Man from the south and other stories - Caldon, Michael; Dahl, Roald (Pearson Education England, 2002)
"Roald Dahl is the master of the unexpected. Things are not always what they seem and nobody should be trusted. In this collection of his short stories we learn some strange lessons about the dangerous world we live in. But you will have to wait until the final pages of each story to discover the last, terrible twist!"--Back cover